Modified starch used as tablet binder from Manihot esculenta Crantz (Fam. Euphorbiaceae) - Dorado, Karren A.; Bautista, Jocelyn S. (Manila College of Pharmacy, University of the Philippines, 1996)
Native cassava starch was chemically modified with the use of acid anhydride and glacial acetic acid. The modified form was evaluated as a binder for placebo tablets in comparison with the native cassava starch. Some fundamental properties of both starches, e.g. water retention capacity and swelling capacity were studied. Tablet hardness, friabilities and disintegration times had been measured. The results showed that the modified form has a better binding ability than the native starch.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, April 1996.
Keywords: Cassava; Starch; Kamoteng-kahoy.